Fundamentalisme Dan Radikalisme: - St. Halimang (IAI Darussalam, 2020)
This article focuses on the existence of fundamentalism and radicalism in terms of Islamic law's discourse construction. This discourse emerges based on the deviation of the ideals of al-Qur'an and al-Hadith. Hence, this article represents fundamentalism and radicalism's patterns and characteristics, whose axis of understanding is based on a religious framework. From this discourse, the researcher identifies this understanding and movement will have the opportunity to emerge in the community. This article concludes that the adherents of fundamentalism and radicalism are stringent in conveying their ideas. They do not hesitate to commit acts of violence in anarchistic form. Nevertheless, they still need to be recognized as part of a societal component that does not leave Islam. Basically, their movement is a form of attitude against the West and modernism, which is considered to emerge to westernization, secularisation, hedonism, pragmatism, uncertainty, and life's emptiness.